Barriers and facilitators to implementing a process to enable parent escalation of care for the deteriorating child in hospital - Gill, F.; Leslie, Gavin; Marshall, A. (Wiley-Blackwell Publishing Ltd., 2018)
Objective: To identify barriers and facilitators to implementing a parent escalation of care process: Calling for Help (C4H). Design: Audits, semi-structured interviews and focus groups guided by the Theoretical Domains Framework. Setting: Australian paediatric hospital where a parent escalation of care process was introduced in the previous 6 months. Participants: Four children, 13 parents, 91 nurses and doctors including Medical Emergency Team (MET) members. Main outcome measures: Parent awareness and involvement in escalating care and factors impacting implementation of C4H. Results: Two audits identified low level of parent awareness (16/88, 19% and 5/85, 6%). Parent involvement in escalation of care was documented in 11/62 (18%) events. The main facilitators included uniformly positive views that C4H was in the child's best interest, acknowledgement that parents had skills to recognize deterioration and would take action. C4H was considered to add to patient safety and being reviewed by the MET was a patient benefit. Key barriers were the low level of awareness, doubt about parent capabilities, concern about parents' information overload, anticipated overuse of resources, staff unease about possible repercussions and anticipated difficulty for parents to question staff with potential negative effects on parent-staff relationships. Overall C4H presents a challenge to traditional hospital hierarchy and culture. Conclusions: Although there was a low level of awareness about C4H in practice, there was in-principle support for the concept. Initial strategies had primarily targeted policy change without taking into account the need for practice and organizational behaviour changes. Using a theoretical approach to identify key factors will enable a targeted approach to implementation.